Effect of habitat factors on the understory plant diversity of Platycladus orientalis plantations in Beijing mountainous areas based on MaxEnt model - Bingchen Wu (Elsevier, 2021)
Habitat factors including topography and soil nutrients affect the formation of understory plant diversity patterns on a small spatial scale. Assessing the combination of suitable habitat factors in areas with abundant understory plant diversity is significant for the management and improvement of plant diversity in the plantations. This study used the maximum entropy model (MaxEnt) to simulate the geographical distribution of the area with abundant understory plant diversity and analyzed the contribution of ten habitat factors to the existence probability of the area with abundant understory plant diversity. The results showed that the regions with medium altitude (292–500 m), gentle slope (13–23 degrees), and high soil organic matter content (>2.3 g/kg) were more likely to breed abundant understory plant diversity. Topographic factors had a dominant effect on the spatial distribution of the understory plant diversity, with the importance of 64.9%. Although the effect of soil nutrient factors on understory plant diversity was less than that of topographic factors, it still made up a large proportion (35.1%). Promoting soil biochemical cycles could be an effective way to increase understory plant diversity. By changing soil organic matter content to 2.3 g/kg, soil available nitrogen to 300 mg/kg, and soil available potassium to 120 mg/kg, the average existence probability of the area with abundant understory plant diversity increased from 0.34 to 0.63. We conclude specific measures including introducing the native broad-leaved tree species such as Cotinus coggygria Scop. and Acer truncatum Bunge into the Platycladus orientalis plantation, logging residue management, and litter management are critical for promoting soil biochemical cycles and thereby increasing understory plant diversity.